Penyuluhan dan Pembuatan Eco-Enzyme dari Limbah Organik Rumah Tangga untuk Peningkatan Kesuburan Tanah di Banjar Panti Gede, Desa Pemecutan Kaja - I Wayan Bhagas Arsadana; Anak Agung Adi Wiryya Putra; I Putu Arya Suartama; Made Bintang Darmawan; I Putu Ditya Ariesannya Baskara (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
Organic household waste remains a significant environmental problem in Indonesia due to the limited utilization of organic waste into value-added products. This condition contributes to environmental pollution and hinders the implementation of sustainable agriculture at the community level. This community service program aimed to enhance community knowledge and skills in processing organic waste into eco-enzyme and applying it as a liquid organic fertilizer to improve soil fertility.The activity was conducted in Banjar Panti Gede, Pemecutan Kaja Village, involving 175 members of the PKK women’s group as participants. The method used a participatory-educative approach through counseling sessions, demonstrations, and direct assistance in producing eco-enzyme using a 3:1:10 ratio (organic waste : brown sugar : water) with a fermentation period of approximately 90 days.The results showed an improvement in community awareness and practical skills in managing organic waste independently. The produced eco-enzyme had a clear brown color, a fresh sour aroma, and a pH of 3–4. The eco-enzyme was applied to home garden plants with a dilution of approximately 10%, which showed improved plant growth responses compared to pre-treatment conditions, particularly in plant height and leaf number.This activity demonstrates that the utilization of eco-enzyme not only contributes to reducing organic waste but also supports soil fertility improvement and sustainable household-level agricultural practices.